2007
DOI: 10.1007/s10147-007-0703-9
|View full text |Cite
|
Sign up to set email alerts
|

Current status of intensity-modulated radiation therapy (IMRT)

Abstract: External-beam radiation therapy has been one of the treatment options for prostate cancer. The dose response has been observed for a dose range of 64.8-81 Gy. The problem of external-beam RT for prostate cancer is that as the dose increases, adverse effects also increase. Three-dimensional conformal radiation therapy (3D-CRT) has enabled us to treat patients with up to 72-76 Gy to the prostate, with a relatively acceptable risk of late rectal bleeding. Recently, intensity-modulated radiation therapy (IMRT) has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Similar studies have found that the mean tumor doses treated with 131 I-tositumomab are 3 Gy [6] and 3.7 Gy in previously untreated patients [7]. In comparison, high doses of standard radiation therapy are needed to achieve clinical responses in solid tumors such as prostate cancer (64.8–81 Gy) [8], lung cancer (40–65 Gy) [9], glioma (60 Gy) [10], breast cancer (50 Gy) [11], ovarian cancer (45 Gy) [5], colorectal cancer (70 Gy) [12] and pancreatic cancer (50.4 Gy) [13]. Based on these clinical experiences, it is generally accepted that solid tumor doses need to reach at least 50 Gy to achieve any clinical benefits.…”
Section: Introductionmentioning
confidence: 93%
“…Similar studies have found that the mean tumor doses treated with 131 I-tositumomab are 3 Gy [6] and 3.7 Gy in previously untreated patients [7]. In comparison, high doses of standard radiation therapy are needed to achieve clinical responses in solid tumors such as prostate cancer (64.8–81 Gy) [8], lung cancer (40–65 Gy) [9], glioma (60 Gy) [10], breast cancer (50 Gy) [11], ovarian cancer (45 Gy) [5], colorectal cancer (70 Gy) [12] and pancreatic cancer (50.4 Gy) [13]. Based on these clinical experiences, it is generally accepted that solid tumor doses need to reach at least 50 Gy to achieve any clinical benefits.…”
Section: Introductionmentioning
confidence: 93%
“…One publication states ''even with IMRT, . a ''perfect'' plan that creates completely homogeneous coverage of the target volume and zero or small dose to the adjacent organs at risk is not always obtained'' (16). Indeed, it is impossible to achieve such a ''perfect'' plan.…”
Section: Understanding the Clinical Utility Of Our Processesmentioning
confidence: 98%
“…Such reviews can be found in recent books 62,63 and review articles. [64][65][66][67] We attempt to predict from what we learned in the last 10 years of development and clinical practice of IMRT the potential direction of further advancement in the near future. IMRT technology consists of planning methods and delivery technologies.…”
Section: Overviewmentioning
confidence: 99%